Ambident Reactivities of Formaldehyde N, N‐Dialkylhydrazones1. Issue 45 (19th September 2013) - Maji, Biplab; Troshin, Konstantin; Mayr, Herbert
<x xml:space="preserve">Abstract</x> What can attack at carbon? With a nucleophilicity N≈7 for attack at the azomethine carbon, formaldehyde hydrazones can undergo noncatalyzed reactions at room temperature with electrophiles that have a reactivity parameter E that is greater than −12.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>